Psychological and emotional factors that influence the entrepreneurial attitude of university students from the Faculty of Engineering of a university - Fernandez-Paredes, Maria; Muñoz-Manrique, Alejandra; Esquicha-Tejada, José; Villanueva-Paredes, Grace Ximena (LACCEI, 2024)
The present study analyzed the psychological and emotional factors influencing the entrepreneurial attitude of students from the Faculty of Physical and Formal Sciences and Engineering at a private university in Arequipa. A total of 296 fourth- and fifth-year students were evaluated, with the results showing a majority of students in Industrial Engineering (40%) and a predominance of males (82%). A significant and direct relationship was found between these factors and entrepreneurial attitude, suggesting that higher levels of psychological and emotional factors are associated with a greater entrepreneurial attitude. The psychological and emotional factors were measured through levels of self-efficacy, self-confidence, achievement motivation, growth mindset, and conflict resolution skills. In contrast, the entrepreneurial attitude was measured through the number of ideas generated, innovation culture, and level of knowledge in entrepreneurship programs